1) 2y/(y^2 -25) - y/(y-5)
Notice that y^2 - 25 factors into (y-5)(y+5).
Multiply the second term by (y+5) on the top and bottom to get a common denominator.
2y/(y^2 -25) - y/(y-5)
= 2y / [(y-5)(y+5)] - y(y+5) / [(y-5)(y+5)]
= [2y - y(y+5)] / [(y-5)(y+5)]
= [2y - y^2 - 5y] / [(y-5)(y+5)]
= (-y^2 - 3y) / [(y-5)(y+5)]
2) The second one is similar.
Factor each denominator.
n^3 - 5n^2 = n^2 (n-5)
n^2 + 5n = n(n+5)
The common denominator will be n^2 (n+5)(n-5)
The first term is missing (n+5) and the second term is missin n(n-5)
2n/(n^3 - 5n^2) + 2/(n^2 +5n)
= 2n(n+5) / [n^2 (n+5)(n-5)] + 2n(n-5) / [n^2 (n+5)(n-5)]
= [2n^2 + 10n + 2n^2 - 10n] / [n^2 (n+5)(n-5)]
= 4n^2 / [n^2 (n+5)(n-5)]
Cancel n^2
= 4 / [(n+5)(n-5)]
2007-01-19 07:17:43
·
answer #1
·
answered by MsMath 7
·
2⤊
0⤋
1)
2y / (y^2-25) - y / (y-5) => Factor the first term, make the 2nd match.
2y / (y-5)(y+5) - y(y+5) / (y-5)(y+5) = > Denominators match. Simplify and combine.
(2y - y^2 - 5y) / (y-5)(y+5) => Combine numerator y terms. I like to pull out the negative
(-1)(y^2 + 3y) / (y-5)(y+5) => Maybe prettier to factor the top
(-y)(y+3) / (y-5)(y+5)
2)
2n / (n^3 - 5n^2) + 2 / (n^2 + 5n) => Pull the n's out of the first term
2 / (n^2 - 5n) + 2 / (n^2 + 5n) => Get a common denominator
2(n^2+5n) / (n^4 - 25n^2) + 2(n^2-5n) / (n^4-25n^2) => Combine
(2n^2 + 10n + 2n^2 - 10n) / (n^4-25n^2) => Drop the 10n, and pull out the n^2
(n^2)(4) / (n^2)(n^2-25) => Cancel.
4 / (n^2-25) => QED
2007-01-19 15:27:01
·
answer #2
·
answered by Brett W 2
·
0⤊
0⤋
1. 2y/y^2 - 25 - y/y-5 = 2/y - 25 - y/y-5 = 2(y-5) -25y(y-5) - y^2/y(y-5) = 2y-10-25y^2 + 125y -y^2 / y^2 - 5y
= (-26y^2 + 127y -10) / y^2-5y
2. 2n/n^3 -5n^2 + 2/n^2 +5n = 2/n^2 - 5n^2 + 2/n^2 +5n
= 4/n^2 - 5n^2 + 5n = (4 - 5n^4 + 5n^3) / n^2
2007-01-19 15:21:54
·
answer #3
·
answered by edge 3
·
0⤊
0⤋
Get a common denominator, which is y^3-5y^2 here
= 2(y-5)/y^2(y-5) - 25(y-5)/(y-5) - y(y-5)/(y-5)
= 2y-10/(y^3-5y^2) - (25y-125)y^2/(y^3-5y^2) - (y^2-5y)y^2/(y^3-5y^2)
= (2y - 10 - 25y^3 - 125y^2 - y^4 - 5y^3)/(y^3-5y^2)
= (y^4 -30y^3 -125y^2 + 2y - 10)/(y^3-5y^2)
Use the common denominator method for the next one as well.
2007-01-19 15:22:19
·
answer #4
·
answered by ohaqqi 2
·
0⤊
0⤋
1.2y/y^2- 25 - y/ y-5If no parentheses clear denom Y*(Y-5)/ Y*(Y-5) : 2Y-10 -25Y*(Y-5) –Y^2 = 2Y-10-25Y^2 + 125Y-Y^2 = 26Y^2 +127Y-10
2007-01-19 16:38:32
·
answer #5
·
answered by PervyRetard 5
·
1⤊
0⤋
1. 2y/(y+5)(y-5) - y/(y-5)
=2y/(y+5)(y-5) - y(y+5)((y+5)(y-5))
=(2y - y(y+5))/((y+5)(y-5))
=(2y - y^2 - 5y)/((y+5)(y-5))
=(-y^2 - 3y)/((y+5)(y-5))
I would solve number two but alas, I must be going for work....
2007-01-19 15:15:44
·
answer #6
·
answered by Robert B 2
·
0⤊
0⤋
Ask a math professional.
2007-01-19 15:16:34
·
answer #7
·
answered by Anonymous
·
0⤊
2⤋